2007
DOI: 10.1111/j.1469-0691.2007.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus producing Panton–Valentine leukocidin as a cause of acute osteomyelitis in children

Abstract: Staphylococcus aureus was identified as the cause of acute childhood osteomyelitis in 19 patients. A single clone of community-acquired methicillin-resistant S. aureus (MRSA) carrying the type IV mecA staphylococcal cassette chromosome and the Panton-Valentine leukocidin (PVL) genes was isolated from five patients. Among the remaining 14 patients, two methicillin-sensitive S. aureus (MSSA) isolates were PVL-positive. The maximal erythrocyte sedimentation rate and C-reactive protein values, and the time require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 14 publications
0
23
0
1
Order By: Relevance
“…A higher erythrocyte sedimentation rate and C-reactive protein concentration have been observed in patients with PVL-positive S. aureus osteomyelitis than in patients infected with PVL-negative S. aureus [15]. However, the reduced amount of infected tissue could have protected our patient from high levels in these analytical parameters [14,16].…”
mentioning
confidence: 61%
“…A higher erythrocyte sedimentation rate and C-reactive protein concentration have been observed in patients with PVL-positive S. aureus osteomyelitis than in patients infected with PVL-negative S. aureus [15]. However, the reduced amount of infected tissue could have protected our patient from high levels in these analytical parameters [14,16].…”
mentioning
confidence: 61%
“…The location of osteomyelitis is similar, with over 60% of infections affecting the femur, tibia or fibula in both PVL-positive and PVL-negative disease (Bocchini et al, 2006). and Sdougkos et al (2007) have reported in S. aureus osteomyelitis that those with PVL-SA had higher biochemical inflammatory markers at presentation and at their peaks and take longer to normalise. Bocchini et al (2006) reported in 89 children that blood cultures were more likely to be positive for S. aureus (67.2% vs 19.2%) and that they were more likely to require ICU admission.…”
Section: Pvl In Osteomyelitismentioning
confidence: 90%
“…In the United States (US), PVL-SA accounts for up to two-thirds of S. aureus related paediatric osteomyelitis (Bocchini et al, 2006, Sdougkos et al, 2007. It is attributed to the USA-300 clone of MRSA which is the most common in the US.…”
Section: Epidemiology Of Pvl Osteomyelitismentioning
confidence: 99%
“…Genes encoding Panton-Valentine leukocidin were found to be present in 59 of 89 S. aureus isolates from cases of acute haematogenous osteomyelitis. The presence of pvl genes is associated with an increased risk of severe infection requiring intensive care, bacteremia and more severe systemic inflammation [39,40]. However, one of the problems with the above studies is that it is unclear how representative these strain collections are of those isolates carried in other establishments and regions across the world, since strain typing was not reported.…”
Section: Genomic Features Of Staphylococci Associated With Bone Infecmentioning
confidence: 99%